Penguatan Profil Pelajar Pancasila Menggunakan Media Pembelajaran Berbasis Digital Di SMA N 1 Sei Bamban - Beslina Afriani Siagian; Hendro Yoni Ganda; Yurni Kristina Pakpahan; Widia Oktavia Manurung; Desi Amelia Sitanggang; Nia Rusadi Silalahi; Silvia Julinda Hutajulu (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
The vision of indonesian education is to realize an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila students. Pancasila student profiles are useful for developing the character and abilities of students in carrying out learning activities. This community service aims to strengthen the profile of Pancasila students using digital-based learning media. The target of this dedication is class XI students at SMA Negeri 1 Sei Bamban. Implementation refers to the preparation, implementation, evaluation, and publication stages. Based on this activity, it was found that students increasingly understood the profile of Pancasila students because they were discussed through digital-based learning media, in this case jamboards. Jamboard allows students to discuss with each other and understand more about the Pancasila student profile.